Modal Sosial Pemuda Putus Sekolah dalam Komunitas Desa Kabupaten Malaka - Stofiani Susana Lima; Abdul Syukur; Nirwaning Makleat; Reschi Vanchristo Ardi Sinlae (Yayasan Literasi Sains Indonesia, 2026)
School dropout is often understood as an indicator of social marginalization that limits young people’s opportunities in economic and social life. However, experiences in many local communities reveal a more complex reality. This study aims to examine how youth without educational credentials maintain social integration through community networks and economic activities in Malaka Regency, East Nusa Tenggara. The research employs a qualitative approach using a case study design. Data were collected through in-depth interviews with fifteen youth without diplomas in three villages, as well as focus group discussions with village officials, managers of Community Learning Centers (PKBM), and parents. The findings indicate that youth without diplomas remain actively involved in community life through participation in customary, religious, and collective activities. Informal economic activities and family networks function as sources of social legitimacy that enable these youth to gain recognition within the community. Although the absence of formal educational credentials limits access to institutional employment, local communities provide alternative mechanisms of social integration through social capital and economic contribution. These findings suggest that the experiences of youth without diplomas cannot be understood solely through a deficit perspective. Instead, they should be viewed as a process of social adaptation mediated by community networks and mechanisms of social recognition.